PENGARUH PENBERIAN PUPUK ORGANIK TERHADAP PRODUKSI TANAMAN BUNCIS (Phaseolus vulgaris L.) - Riza, Fatma - (STKIP PGRI Sumbar, 2014)
Fertilizer is a materials used to repairing fertility of farm land. Target of fertilization to adding availibility element of hara in farm land so plant grow and expand well and maximal productive. Chaff ash, chickenrun fertilizer, cow shed fertilizer, and sheep fold fertilizer are organic fertilizer that can repaire nature of farm land so that can improve beans productive. This research have been done at June â July 2013. To the purpose of this research to know the influence of organic fertilizer for increasing the beans (Phaseolus vulgaris L.) production. The research used the Randomized Complete Block Design (RCBD) with 5 treatments and 5 replication. The treatment are A= control, B= chaff ash, C= chickenrun fertilizer, D= cow shed fertilizer, E= sheep fold fertilizer. The result of research analysed with RCBD at 5% and 1%. Beans productive the perceived is amount of beans and wet wight of beans. The result of research show that organic fertilizer using organic fertilizer of chaff ash 150 gram/plant, chickenrun fertilizer 150 gram/plant, cow shed fertilizer 150 gram/plant, and sheep fold fertilizer 150 gram/plant do not giving influence to amount of beans and wet weight of beans.